2016
DOI: 10.3402/gha.v9.31440
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural prevalence of diabetes and pre-diabetes and risk factors associated with diabetes in Tanzania and Uganda

Abstract: BackgroundThe increase in prevalence of diabetes and pre-diabetes in sub-Saharan Africa underlines the importance of understanding its magnitude and causes in different population groups. We analyzed data from the Africa/Harvard Partnership for Cohort Research and Training (PaCT) studies to determine the prevalence of diabetes and pre-diabetes and risk factors associated with diabetes.MethodologyParticipants were randomly selected from peri-urban (n=297) and rural (n=200) communities in Uganda, and teachers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 18 publications
8
81
4
1
Order By: Relevance
“…The observed differences in PA status in rural and urban settings have also been reported previously and reflect the rural-urban differences in NCDs prevalence [27][28][29]. Different studies conducted in Africa have consistently reported higher prevalence of diabetes, hypertension, and cardiovascular risk factors in urban compared to rural settings [27][28][29]. In addition, we observed a negative linear relationship between PA levels and a number of cardio metabolic risk factors including high blood pressure.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The observed differences in PA status in rural and urban settings have also been reported previously and reflect the rural-urban differences in NCDs prevalence [27][28][29]. Different studies conducted in Africa have consistently reported higher prevalence of diabetes, hypertension, and cardiovascular risk factors in urban compared to rural settings [27][28][29]. In addition, we observed a negative linear relationship between PA levels and a number of cardio metabolic risk factors including high blood pressure.…”
Section: Discussionsupporting
confidence: 68%
“…This could render GPAQ less appropriate for in between groups' evaluation, meaning that some of the comparisons between groups have been interpreted with caution. Despite these limitations, studies employing different PA questionnaires and/or objective PA assessment have reported similar trends of PA [27][28][29]. This means that while the observations presented in the current study require further verification, the overall PA status reported reflects the real situation.…”
Section: Study Limitationsmentioning
confidence: 67%
“…Most participants 272(97.49%), were married. In the study by Chiwanga F. S. et al 9 the highest number of participants belonged to the age group of 30-39 years followed by the age group of 40 -49. The number of female participants (80, 51.6%) was more than males (75, 48.4%).…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, diabetes and hypertension are commonly associated with each other and frequently co‐occur. Commonly shared risk factors include, but are not limited to, physical inactivity, obesity, unhealthy diet, heavy alcohol use and smoking; those who live in rural areas are more likely to have diabetes and hypertension compared with those who live in urban areas …”
Section: Introductionmentioning
confidence: 99%
“…Commonly shared risk factors include, but are not limited to, physical inactivity, obesity, unhealthy diet, heavy alcohol use and smoking; those who live in rural areas are more likely to have diabetes and hypertension compared with those who live in urban areas. [3][4][5][6] Among older adults, both diabetes and hypertension are independent risk factors for frailty, cardiovascular disease and chronic kidney disease; [7][8][9] and co-occurring diabetes and hypertension has synergistic effects on morbidity and mortality. Co-occurring diabetes and hypertension increases all-cause mortality by 38% and cardiovascular disease by 70%.…”
Section: Introductionmentioning
confidence: 99%